(untitled) (AYUSHDHARA, 2025)
Background: Gridhrasi is a pain dominant Vata Nanatmaja Vyadhi leading to Gridha (Vulture) like gait with symptoms like Stambha, Ruk, Toda and Spandana in Sphika, Kati, Prishtha, Uru, Janu, Jangha and Pada in ascending manner. Gridhrasi is comparable to Sciatica in contemporary medicine. In India lifetime incidence is reported to be between 10% to 40% and an annual incidence of 1 to 5%. Only conservative measures that provide temporary pain relief or surgery with adverse effects are available. While Ayurveda offers a variety of scientific approach out of which Siraveda and Agnikarma are thought to provide quick pain relief. Aims: To compare the effect of Siravedha and Conductive Agnikarma in the management of Gridhrasi. Materials and Methods: This is parallel group open randomized clinical trial. A total of 40 patients, divided randomly in two groups, were treated by Siravedha in 20 patients and Conductive Agnikarma in 20 patients. Siravedha was done from prominent vein near Antara Kandara Gulpha. Conductive Agnikarama was done over Sciatic nerve roots L4 – S3 on either side by Suvarna Shalaka. The Wilcoxon’s Signed-Rank Test was carried out for all non-parametric data (i.e., for subjective criteria) within the group. Mann Whitney test was adopted for comparing the subjective parameter between two groups. Students paired ‘t’ test was applied for the objective parameters. Results: On an individual basis, both groups have alleviated the cardinal sign and symptoms of Gridhrasi. After Siravedha 63.15% patients showed moderate improvement and 21.05% had mild relief. In Conductive Agnikarma, 60% patients had moderate improvement whereas 20% patient had marked and mild improvement each. Conclusion: Siravedha gives slightly better effect than Conductive Agnikarma in the management of Avaranjanya Vata-Kaphaj Gridhrasi.